2020
DOI: 10.3389/fphys.2020.00568
|View full text |Cite
|
Sign up to set email alerts
|

Walking With Leg Blood Flow Restriction: Wide-Rigid Cuffs vs. Narrow-Elastic Bands

Abstract: Background: Blood flow restriction (BFR) training is becoming a popular form of exercise. Walking exercise in combination with pressurized wide-rigid (WR) cuffs elicits higher cardiac workload and a vascular dysfunction due presumably to reperfusion injury to the endothelium. In contrast, narrow-elastic (NE) BFR bands may elicit different hemodynamic effects. Therefore, we compared the acute cardiovascular responses to two distinct forms of BFR training during light-intensity exercise. Methods and Results: 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 24 publications
(42 reference statements)
0
30
2
Order By: Relevance
“…Whilst participants reported differences in discomfort in the present study, no differences in RPE were reported. This differs from a previous study indicating that wider cuffs resulted in greater RPE values when compared to narrower cuffs (Stray‐Gundersen, et al, 2020). An important distinction, however, is that the previous study used arbitrary pressures which may have resulted in a different restrictive stimulus between cuffs as indicated by differing heart rates and blood pressure values between cuffs (Stray‐Gundersen, et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Whilst participants reported differences in discomfort in the present study, no differences in RPE were reported. This differs from a previous study indicating that wider cuffs resulted in greater RPE values when compared to narrower cuffs (Stray‐Gundersen, et al, 2020). An important distinction, however, is that the previous study used arbitrary pressures which may have resulted in a different restrictive stimulus between cuffs as indicated by differing heart rates and blood pressure values between cuffs (Stray‐Gundersen, et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…This differs from a previous study indicating that wider cuffs resulted in greater RPE values when compared to narrower cuffs (Stray‐Gundersen, et al, 2020). An important distinction, however, is that the previous study used arbitrary pressures which may have resulted in a different restrictive stimulus between cuffs as indicated by differing heart rates and blood pressure values between cuffs (Stray‐Gundersen, et al, 2020). Indeed, others have shown that different absolute pressures result in altered perceptual responses (Spitz, et al, 2019, 2021), further detailing that the magnitude of applied pressure may alter perceptual responses.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As with most research designs, there are an infinite number of combinations of potentially confounding issues related to participant selection for the protocol, like age, sex, training status, health status, nutritional status, hormonal status, etc., but with blood flow restriction protocols, many other factors must also be considered. These additional factors could include the type of cuff used to induce the restriction pressure (width of the cuff, type of material, pneumatically controlled cuffs or tension wraps or bandages applied based on perceived discomfort; Loenneke et al, 2014c ; Buckner et al, 2017 ; Stray-Gundersen et al, 2020 ), initial pressure/tightness of the cuffs before inflation ( Karabulut et al, 2011a , 2014 ), the restrictive pressure used (absolute, relative, percent of total restrictive pressure, intermittent pressure, continuous pressure; Murray et al, 2020 ), the composition (fat and muscle mass; Karabulut et al, 2014 ) and size (circumference or girth) of the limb being restricted ( Loenneke et al, 2014a ), the mode of exercise (walking, cycling, resistance training, absolute loads, relative loads, contraction types – isometric, isotonic, isokinetic), the protocols used if exercise is required (number of repetitions, number of sets, muscle groups, cadence of the concentric and eccentric portions of the movement, time under tension), and if the responses are acute or due to prolonged training (how many sessions, days, weeks, etc.).…”
Section: Limitations From Previous Studies and Current Gaps In The Research Literaturementioning
confidence: 99%
“…Previous studies have found that exercise with BFR causes physiological adaptation (increased heart rate), similar to high-intensity exercise in obese adults (Karabulut et al, 2017), athletes (Willis et al, 2016), and hypertensive elderly people (Barili et al, 2018). Regarding vascular function, BFR does not cause damage to the blood vessels during either walking or resistance exercises (Stray-Gundersen et al, 2020;da Cunha et al, 2020). Aerobic exercise with BFR could significantly increase the heart rate when compared to aerobic exercise alone (Barili et al, 2018;Thomas et al, 2018).…”
Section: Introductionmentioning
confidence: 99%